DISKRIMINASI RASIAL DALAM KASUS GEORGE FLOYD DI AMERIKA BERDASARKAN INTERNATIONAL CONVENTION ON THE ELIMINATION OF ALL FORMS OF RACIAL DISCRIMINATION (ICERD) - Andry Syaharani Wiguna; Ayu Nrangwesti (Faculty of Law, Universitas Trisakti, 2023)
This study discusses the case of racial discrimination experienced by George Floyd in America based on the International Convention on the Elimination of All Forms of Racial Discrimination (ICERD). The research questions include how the American government addresses racial discrimination against black citizens and resolves the George Floyd case as a violation of human rights. In this study, the authors use normative research methods with literature reviews, fully relying on secondary data to describe the situation and events. The results of this research indicate that the American government has actually taken steps to address discrimination. Examples include Article 2 of the Universal Declaration of Human Rights (UDHR), Articles 2, 4, and 5 of the International Convention on the Elimination of All Forms of Racial Discrimination (ICERD), Amendment IV of the Bill of Rights 1791, Article 1 Sections 2 and 9 of the U.S. Constitution 1787, and Title IV of the Civil Rights Act of 1964. These measures are taken to protect and provide racial equality for black individuals from all aspects. In George Floyd's case, a more just implementation of the law is necessary to prevent further police violence against black individuals.